2017
DOI: 10.18203/2320-1770.ijrcog20174075
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of spontaneous posterior wall rupture in an unscarred uterus during labour

Abstract: Uterine rupture is a dreaded catastroph in obstetrics with a high incidence of maternal and fetal morbidity. In developing Country, the overall prevalence widely varies from 1 in 2,000 to 1 in 200 deliveries. Uterine rupture in an unscarred uterus is a rare event and only a finger countable cased have been reported on posterior rupture of uterus in unscarred uterus. We here presenting a case of spontaneous posterior rupture of an unscarred uterus. Our patient was 38 years old grand multipara, a 6th gravida fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Spontaneous uterine rupture in an unscarred uterus is a rare event that can lead to maternal and fetal morbidity and mortality. The incidence of rupture of unscarred uteri is 0.0175% to 0.005% of pregnancies [ 1 ]. Causes of uterine rupture include trauma, congenital weakness of the myometrium (e.g., Ehlers-Danlos type IV) [ 2 ], acquired weakness secondary to prolonged labor or uterotonic drugs [ 3 , 4 ], or uterine cavity overdistension due to multiple gestation, high parity, or uterine anomalies [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous uterine rupture in an unscarred uterus is a rare event that can lead to maternal and fetal morbidity and mortality. The incidence of rupture of unscarred uteri is 0.0175% to 0.005% of pregnancies [ 1 ]. Causes of uterine rupture include trauma, congenital weakness of the myometrium (e.g., Ehlers-Danlos type IV) [ 2 ], acquired weakness secondary to prolonged labor or uterotonic drugs [ 3 , 4 ], or uterine cavity overdistension due to multiple gestation, high parity, or uterine anomalies [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Unscarred pregnancy uterine rupture is an uncommon occurrence that is thought to take place in 1/5700 to 1/20,000 pregnancies. 1,4 The anterior lower portion of the uterus is where the majority of ruptures in unscarred uteruses take place; posterior wall ruptures are scarce. Even more atypical is posterior uterine wall rupture, which has only a few instances published in the literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…uterine rupture in unscarred or intact uteruses. 4,8,11,12 It has been observed that fetal malposition, such as occipitoposterior position and malpresentation with a transverse line, can cause posterior uterine ruptures. 8 Clinical manifestations of uterine rupture may include acute or abnormal maternal abdominal pain, tachycardia, vaginal bleeding with shock, loss of uterine contractility, and sometimes blood-tinged urine.…”
mentioning
confidence: 99%
See 2 more Smart Citations